Comparison of Civics and Social Studies Learning Design Models in Various Countries at the Elementary School Level - Novalina Indriyani; Yeni Erita; Mayrisa Undari; Wiwit Sanjaya (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2022)
Learning design models are used so that learning activities run smoothly and are varied. Most teachers still have not implemented learning models, so teachers are less able to stimulate students in finding and solving problems contained in learning material. This study aims to determine the Civics and Social Studies learning design models that are often used in Indonesia and in various countries at the elementary school level. Writing this article using qualitative research with a descriptive approach. Data collection was carried out by means of a literature study. The results of the study found that without designing and using the right model, learning activities could fail, even though the material prepared was as interesting as possible. The selection of learning design models can be seen from the conditions, needs, nature of teaching materials, characteristics of students, and learning media. In Indonesia, the learning design models that are often used are the ADDIE, ASSURE, and Dick and Carey. While the learning design models implemented by several countries are the STEM model (America, South Korea and Finland), the DMKK model (Japan), the Discovery Learning (Marland and Turkey), and the Mind Mappingy (Arabia, Turkey and Australia). Teachers are guided to be able to apply learning design models when learning activities take place in order to achieve the expected learning objectives.